Late antenatal care utilization in Ethiopia: The effect of socio-economic inequities and regional disparities. - Belayneh Mengist; Bekalu Endalew; Gedefaw Diress; Amanuel Abajobir (Public Library of Science (PLoS), 2022)
Antenatal care (ANC) is one of the most crucial components of maternal health care services. However, less than two-third of pregnant women receive ANC at least once and only 32% had at least 4 ANC visits in Ethiopia. There is dearth of nationally representative data that indicate changes in utilization of ANC services at the end of health sector transformation plan I period (HSTP I) in the country. Therefore, the present study aimed to investigate utilization of ANC the effect of socio-economic inequities and regional disparities in Ethiopia. The 2019 Ethiopian Mini Demographic and Health Survey data were used. A total of 5753 women in the reproductive age who gave live births in the five years preceding the survey were used for this study. Multivariable logistic regression model was fitted to identify factors associated with ANC booking. This study indicated that 74% women had at least one ANC visit during their last pregnancy of which four out of ten did not receive the recommended 4+ visits. The proportion of women who had late ANC booking (i.e., first ANC visit to health facility after 4 months of pregnancy) was found to be 32% and significant disparities were observed across regions. Rural residency (adjusted OR (AOR): 1.62, 95% CI (1.28, 2.05)), being wealth (AOR: 0.69, 95% CI (0.55, 0.85)), education (AOR: 0.25, 95% CI (0.15, 0.40)) and being grand multi-parity (AOR: 1.35, 95% CI (1.005, 1.83)) were significantly associated with late ANC booking. ANC services utilization is far behind its targets and the proportion of pregnant women entering ANC late is high. It is necessary to intensify efforts to raise awareness about the need of early ANC initiation, particularly in rural areas.